Comparative Evaluation Of The Efficacy And Frequency Of Intraoperative And Postoperative Complications In The Treatment Of Mandibular Calculi By Retrograde Intrarenal Surgery And Percutaneous Nephrolithotripsy - Magomedrasulovich, Kanbulatov Abdulla; Magomedovna, Gulieva Saidat; Imangazalievich, Imangazaliev Magomedsaygid; Gadjievna, Isaeva Patimat; Nadyrovich, Ramazanov Khanmagomed; Ayazbegovna, Mugadova Patimat; Magomedovna, Idrisova Patimat; Yunusovna, Gazieva Amina; Basirovna, Mollaeva Laila; Aligadzhievna, Magomedtaminova Khadizhat; Shakhbanovna, Kurbanova Ravza (Journal of Neonatal Surgery, 2025)
The aim of the study was to compare the effectiveness and frequency of intraoperative and postoperative complications in the treatment of lower renal calyx stones using retrograde intrarenal surgery (RIRX) and percutaneous nephrolithotripsy (PerkNL). 79 patients were included in the study, of which 41 patients underwent CPR and 38 underwent CPR. The degree of stone removal (stone-free rate, SFR), duration of surgery and hospitalization, frequency of complications (on the Clavien-Dindo scale), as well as the need for repeated interventions were assessed. PerkNL demonstrated a higher rate of complete rehabilitation from stones (92.1% versus 78.0% for RIRH, p < 0.05), but was accompanied by a higher incidence of complications, including bleeding and the need for blood transfusions. At the same time, RIRX showed less invasiveness, shorter hospital stay (on average 2.1 days versus 4.6 days), and a favorable safety profile. Repeated interventions were required more often after the RIRH (14.6% vs. 2.6%).PerkNL provides a higher effectiveness in the treatment of stones of the lower calyx of the kidney, especially if their size is more than 20 mm, but it is associated with greater traumatism. RIRX can be considered as the preferred method in patients with stones <15 mm and favorable anatomy of the pelvic system